Emerging roles of cytomegalovirus-encoded G protein-coupled receptors during lytic and latent infection - Frank, Theresa; Niemann, Ina; Reichel, Anna; Stamminger, Thomas (Medical Microbiology and Immunology, 2019)
Cytomegaloviruses (CMVs) have developed multiple diverse strategies to ensure their replicative success and to evade immune recognition. Given the fact that G protein-coupled receptors (GPCRs) are key regulators of numerous cellular processes and modify a variety of signaling pathways, it is not surprising that CMVs and other herpesviruses have hijacked mammalian GPCRs during their coevolution. Human cytomegalovirus (HCMV) encodes for four viral GPCR homologues (vGPCRs), termed US27, US28, UL33, and UL78. Although HCMV-encoded GPCRs were first described in 1990, the pivotal functions of these viral receptor proteins were detected only recently. Here, we summarize seminal knowledge on the functions of herpesviral vGPCRs with a focus on novel roles of cytomegalovirus-encoded vGPCRs for viral spread and the regulation of latency.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Cell signaling; Chemokine receptor; Cytomegalovirus; G protein-coupled receptor (GPCR); US28